1973
DOI: 10.1038/bjc.1973.145
|View full text |Cite
|
Sign up to set email alerts
|

Some EPR Signals in Tumour Tissue

Abstract: Summary.-Normal and tumour tissues from rats, blood from normal and tumour bearing rats, and normal human blood were examined using the electron paramagnetic resonance (epr) technique. At low temperature a triplet epr signal, which is known to be produced by a NO -haemoprotein complex, was detected in some tumour samples and in decaying normal liver. At room temperature all of the tumour samples examined gave a doublet signal. This signal was also detected in blood but not in other normal tissues. The signal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The characteristic doublet signal of AscR (Dodd 1973) was detected. AscR showed an asymmetric doublet signal with a line width of 0.18 mT centered at g = 2.007.…”
Section: Inhibition Of Cell Proliferation By Higher Doses Of Asc or Amentioning
confidence: 99%
“…The characteristic doublet signal of AscR (Dodd 1973) was detected. AscR showed an asymmetric doublet signal with a line width of 0.18 mT centered at g = 2.007.…”
Section: Inhibition Of Cell Proliferation By Higher Doses Of Asc or Amentioning
confidence: 99%
“…More recent studies have shown that this radical is present in a wide variety of malignant tissues at a higher concentration than in the corresponding normal tissues (Dodd, 1973). Consequently a systematic study has been made of the changes in the ascorbyl radical concentration occurring in the blood, spleen and liver during a murine myeloid leukaemia.…”
mentioning
confidence: 99%
“…The nature of each of these and their probable mode of formation is discussed below. The narrow doublet signal, seen only in unfrozen samples of tissue has previously been assigned to the ascorbyl radical (Dodd, 1973). This signal, although not detected in normal muscle, is readily observed in implanted tumours (Dodd & Silcock, 1976) and implants of normal tissue (Dodd & Silcock, 1980).…”
Section: Discussionmentioning
confidence: 91%
“…Results 9 GHz ESR of tissues The characteristic doublet signal (Figure 1) of the ascorbyl radical (Dodd, 1973) was detected at room temperature in the samples of implanted muscle, but was not detected in normal muscle. However, when removed and sampled under anoxic conditions, the implanted muscle showed no signal until exposed to air.…”
Section: Methodsmentioning
confidence: 96%